Effect of the pig rearing system on the final volatile profile of Iberian dry-cured ham as detected by PTR-ToF-MS - Sánchez del Pulgar, J; Soukoulis, C; Carrapiso, A I; Cappellin, L; Granitto, P; Aprea, E; Romano, A; Gasperi, F; Biasioli, F (Meat Science, 2013)
The volatile compound proﬁle of dry-cured Iberian ham lean and subcutaneous fat from pigs fattened outdoors on acorn and pasture (Montanera) or on high-oleic concentrated feed (Campo) was investigated by proton transfer reaction time-of-ﬂight mass spectrometry. In addition to the usual proton transfer ionization the novel switchable reagent ions system was implemented which allows the use of different precursor ions (H3O+ , NO+ and O2 + ). The analysis of the lean and subcutaneous fat volatile compounds allowed a good sample discrimination according to the diet. Differences were evident for several classes of compounds: in particular, Montanera hams showed higher concentrations of aldehydes and ketones and lower concentrations of sulfur-containing compounds compared to Campo hams. The use of NO+ as precursor ion conﬁrmed the results obtained with H3O+ in terms of classiﬁcation capability and provides additional analytical insights.
Keywords: aldehydes; Aldehydes: analysis; Animal Feed; Animal Husbandry; Animal Husbandry: methods; Animals; diet; Dietary Fats; Dietary Fats: analysis; Dietary Fats: pharmacology; Dry cured ham; Ions; Ketones; Ketones: analysis; Mass spectrometry; Mass Spectrometry: methods; meat; Meat: analysis; Nuts; Oleic Acid; Oleic Acid: pharmacology; Poaceae; Proton transfer reaction mass spectrometry; Quercus; Rearing system; subcutaneous fat; Subcutaneous Fat: metabolism; Sulfur Compounds; Sulfur Compounds: analysis; Swine; Switchable reagent ions; Time of flight; Volatile Organic Compounds; Volatile Organic Compounds: analysis